ANALISIS PENGARUH KECEPATAN MOBILITAS USER TERHADAP QOS DIWLAN MENGGUNAKAN OPNET MODELER - Hikmaturokhman, Alfin; Fatonah, Nurul; Cahyadi, Eko Fajar (Proceeding SENDI_U, 2015)
Clustering is a technique used to analyze data either in machine learning, data mining, pattern recognition,image analysis and bioinformatics. So as to produce useful information need for an analysis of data usingclustering process because data has a lot of variety and quantity. In this case the researchers will use the KMeansmethod in which these methods into an efficient and effective algorithms to process data with the varietyand number of lots. K-means algorithm has a problem in determining the best number of clusters. So in thispaper the researchers will conduct research to search for the best number of clusters in K-means method. Thereare many ways to determine this, one of them with methods Elebow. The determination of these methods seenfrom the graph SSE (Sum Square Error) of some number of clusters. Results from this study will be the basis fordetermining the number clusters in the process clustering with K-Means method in a case study, and this casestudy will be conducted at the institute STAHN (Sekolah Tinggi Agama Hindu Negeri) Tampung PenyangPalangkaraya.Keywords: clustering, k-means, method elbow, SSE (Sum Square Error)